2017
DOI: 10.1016/j.ajpath.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Human Effector Memory T Helper Cells Engage with Mouse Macrophages and Cause Graft-versus-Host–Like Pathology in Skin of Humanized Mice Used in a Nonclinical Immunization Study

Abstract: Humanized mice engrafted with human hematopoietic stem cells and developing functional human T-cell adaptive responses are in critical demand to test human-specific therapeutics. We previously showed that humanized mice immunized with long-lived induced-dendritic cells loaded with the pp65 viral antigen (iDCpp65) exhibited a faster development and maturation of T cells. Herein, we evaluated these effects in a long-term (36 weeks) nonclinical model using two stem cell donors to assess efficacy and safety. Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…A surprising outcome of our study in fully humanized mice was the substantially increased concentrations of human cytokines in plasma of three of seven CAR‐positive animals concomitantly with B‐cell aplasia and the signs of neurotoxicity in one mouse. Human myeloid and CD4 + T cells are the likely source for the released cytokines (Tanaka et al , ; Sundarasetty et al , ). The cytokine profile resembled that of CAR T‐cell‐treated patients suffering from CRS (Hay et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…A surprising outcome of our study in fully humanized mice was the substantially increased concentrations of human cytokines in plasma of three of seven CAR‐positive animals concomitantly with B‐cell aplasia and the signs of neurotoxicity in one mouse. Human myeloid and CD4 + T cells are the likely source for the released cytokines (Tanaka et al , ; Sundarasetty et al , ). The cytokine profile resembled that of CAR T‐cell‐treated patients suffering from CRS (Hay et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to HSCT, mice were sublethally irradiated (450 cGy) using a [137 Cs ] column irradiator (Gammacell 3000 Elan; Best Theratronics, Ottawa, ON, Canada). 4 h after irradiation, 1.5–2.0 × 10 5 human CD34 + hematopoietic cells isolated from female donor umbilical CB were administrated to each mouse trough the tail vein as described ( 20 , 24 ). We had previously shown that immune reconstitution in female mice recipients was faster than in males ( 25 ) and we, therefore, used female donors to avoid any putative immune responses against antigens expressed in the Y chromosome of male recipients.…”
Section: Methodsmentioning
confidence: 99%
“…CD14 + monocytes were isolated at high purity (from the same CB units used as source of CD34 + HSCs) by immune-magnetic beads (Miltenyi Biotec, Bergisch Gladbach, Germany) and cryopreserved. CD14 + cells were used for the generation of iDCpp65 after transduction with a tricistronic integrase-defective lentiviral vector co-expressing human cytokines GM-CSF/IFN-α and the HCMV-pp65 protein as described (IDLV-G2a-pp65) ( 20 , 24 ). In short, monocytes were pre-conditioned with recombinant human GM-CSF and IL-4 (both 50 ng/ml; Cellgenix, Freiburg, Germany) for 8 h prior to lentiviral gene transfer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were transplanted with CB-CD34 + cells using previously described techniques. [32][33][34][35] Briefly, human CD34 + cells were isolated after two rounds of positive selection with MACS magnetic beads (CD34 MicroBead Kit; Miltenyi Biotec). At the age of 4-6 weeks, mice were sublethally irradiated with 450 cGy using a 137 Cs-column irradiator (Gammacell 3000 Elan; Best Theratronics, Ottawa, Canada).…”
Section: Generation Of Humanized Mice Infected With Hcmvmentioning
confidence: 99%